Masalah Mahasiswa Keperawatan Dalam Menyelesaikan Tugas Akhir - Lotulung, Christa Vike (Fakultas Ilmu Keperawatan Universitas Klabat, 2024)
The demands of final assignments often constitute an academic burden that is considered difficult by most students, making it a big challenge to complete the final assignment. There are so many factors that can influence a student's success in completing their final assignment. This research aims to explore information related to the problems faced by final-year nursing students in completing their theses. A quantitative design with a descriptive approach was carried out in carrying out this research involving 200 student respondents from a private university in North Sulawesi. The instrument used by researchers in collecting data was a questionnaire with online open questions. The data was analyzed using a frequency distribution model using statistical tools on a computer. Based on the perceptions and experiences of respondents in the questionnaire answers, the results of this research found several dominant problems faced by students both internally and externally, namely related to feeling lazy and lack of motivation, busyness with the demands of other courses, lack of support from friends and a conducive environment, poor understanding. still lacking in terms of research methods and data analysis, as well as the consul's busy schedule and schedule not being compatible with the supervisor's lecturer. It is important for students to develop strategies that suit their needs, increase motivation, develop necessary academic skills, or plan their time more efficiently. Apart from that, educational institutions can also provide greater support in the form of academic guidance, access to resources, or support programs to help students overcome the challenges they face regarding completing their final assignments. Tuntutan tugas akhir seringkali menjadi beban akademik yang dianggap sulit oleh sebagian besar mahasiswa sehingga menjadi tantangan yang besar dalam menyelesaikan tugas akhir. Begitu banyak faktor yang dapat mempengaruhi keberhasilan mahasiswa dalam menyelesaikan tugas akhir. Penelitian ini bertujuan untuk menggali informasi terkait masalah-masalah yang dihadapi oleh para mahasiswa keperawatan tingkat akhir dalam menyelesaikan skripsi. Desain kuantitatif dengan pendekatan deskriptif telah dilakukan dalam pelaksanaan penelitian ini yang melibatkan 200 responden mahasiswa dari salah satu universitas swasta di Sulawesi Utara. Instrument yang digunakan peneliti dalam pengumpulkan data adalah kiuesioner dengan pertanyaan terbuka secara daring. Data dianalisis dengan model distribusi frekuensi menggunakan perangkat satistik dalam computer. Berdasarkan persepsi dan pengalaman responden dalam jawaban kuesioner, hasil penelitian ini menemukan beberapa masalah dominan yang dihadapi mahasiswa baik secara internal maupun eksternal, yaitu terkait rasa malas dan kurang motivasi, kesibukan dengan tuntutan mata kuliah lainnya, kurangnya dukungan teman dan lingkungan yang kondusif, pemahaman yang masih kurang dalam hal metode dan analisis data penelitian, serta kesibukan dan jadwal konsul yang tidak sesuai dengan dosen pembimbing. Penting bagi mahasiswa untuk mengembangkan strategi yang sesuai dengan kebutuhan, meningkatkan motivasi, mengembangkan keterampilan akademik yang diperlukan, atau merencanakan waktu dengan lebih efisien. Selain itu, institusi pendidikan juga dapat memberikan dukungan yang lebih besar dalam bentuk bimbingan akademik, akses terhadap sumber daya, atau program-program pendukung untuk membantu mahasiswa mengatasi tantangan yang dihadapi terkait penyelesaian tugas akhir.